KONSTRUKSI MAKNA PAGEANT BAGI PRIA DI KOTA PEKANBARU YANG PERNAH MENGIKUTI AJANG MALE PAGEANT DALAM PERSPEKTIF FENOMENOLOGI - Dira Rawina Windasari; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The emergence of pageant is a new phenomenon in Indonesia that has attracted the interest of productive Indonesians to follow. The pageant event is identical as a beauty event that is for women. Along with the development of the era of modernization, gender equality is increasingly widespread to achieve an achievement began popping special pageant event for men called the male pageant. The development of the pageant`s male event itself is already visible in Pekanbaru City. It can be seen from the start of the number of male pageant event ever held in this city. This study aims to find out how the motives of men in Pekanbaru follow the male pageant, and how they interpret the pageant event itself.This research uses qualitative research method with phenomenology approach. Research subjects consisted of 4 men in Pekanbaru City who had followed the male pageant event chosen using snowball technique. Data collection is done through in-depth interviews, observation and documentation. To test the validity of the data the author using the method of extension of participation and triangulation.The result of this research shows that male motive in Pekanbaru City follows the male pageant consisting of past motive (because motive) and future motive (in order to motive). The motives of the past (because Motive) men in Pekanbaru follow the pageant's male event is (1) family motivation (2) boast of the parents (3) measure the self-tray (4) add activity. While the motive of the future (in order to motive) men in Pekanbaru follow the pageant male event is (1) to increase experience and insight (2) career supporters (3) to increase the relationship. Meaning pageant which is interpreted by man in Pekanbaru City who ever follow the pageant male event is (1) event of self development (2) positive event (3) event that becomes role model.Keyword: meaning construction, pageant, male pageant, motive